GAMBARAN STRATIFIKASI SOSIAL DALAM DRAMA OTHELLO KARYA SHAKESPEARE - EMAN, KARINA JACQUALINE (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT This research entitled â€œGambaran Stratifikasi Sosial dalam Drama Othello Karya Shakespeareâ€ is intended to give explanation about the connection between the aspects of extrinsic, in this case, the sociological aspects such as social stratification; â€œstatusâ€ and â€œhonorâ€ and intrinsic aspects which mainly stressing on the role of characters including their expressions, actions, and dialogues. The objectives of the research are to identify and analyze the methods applied by Shakespeare to describe the social stratification available in drama Othello. The methodology conducted consists of 3 phases namely; Preparation, Data Collection, and Data Analysis. The data were taken from the text Othello through â€œcontent analysisâ€, classified into intrinsic elements such as characters, action, expression, and dialog. In terms of analysis, a descriptive method is applied supported by data on the side of sociology namely social stratification (status and honor) to analyze the intrinsic elements such as expression, action, and dialog which found in the interaction among characters. The research findings show that â€œSocial Stratificationâ€ is admitted alive by Shakespeare through â€œOthelloâ€. It depicted in the interaction among character, expression, action, and dialogue in the drama. Â Keywords: Othello, Social Stratification, characters, action, expression, dialog, content analysis, status, honor.